Transcriptomic and Metabolomic Profiling Reveals the Effect of LED Light Quality on Fruit Ripening and Anthocyanin Accumulation in Cabernet Sauvignon Grape - Zhang, Peian; Lu, Suwen; Liu, Zhongjie; Zheng, Ting; Dong, Tianyu; Jin, Huanchun; Jia, Haifeng; Fang, Jingggui (Frontiers in Nutrition, 2021)
Different light qualities have various impacts on the formation of fruit quality. The present study explored the influence of different visible light spectra on the formation of quality traits and their metabolic pathways in grape berries. We used pre-veraison ‘Cabernet Sauvignon’ clusters as the research material and applied metabolomics and transcriptomics methods to study the effects of red light, green light, blue light, white light, and control conditions (no light treatment) on anthocyanin components, soluble sugars, organic acids, volatiles components, and other grape properties. We found that blue light and red light had different effects on the berries. Compared with white light, blue light significantly increased the anthocyanins (malvidin-3-O-glucoside and peonidin-3-O-glucoside), volatile substances (alcohols and phenols), and soluble sugars (glucose and fructose), reduced the organic acids (citric acid and malic acid), whereas red light achieved the opposite effect. Using weighted gene co-expression network analysis (WGCNA) of 23410 highly expressed genes, two modules significantly related to anthocyanins and soluble sugars were screened out. These findings help elucidate the characteristics of different light qualities on the formation of plant traits and can inform the use of supplemental light in the field and after harvest to improve the overall quality of fruit.